Factors Affecting on Job Performance - Gde Dananjaya Danika Darmawan; Justine Tanuwijaya (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The demand for coal commodities in 2023 will increase. The increase in coal demand has caused the coal production target to be achieved in 2023 is also increase. Every mining company should have optimal human resources that are able to compete with other companies. Employees who are in a company usually want job satisfaction, to be able to improve their performance. Giving rewards, job training, promotion, motivation are several factors that can increase job satisfaction to support employee performance. This study aims to determine the effect to analyze and examine the effect of reward, job training, promotion, motivation, on job satisfaction, and examine the effect of job satisfaction on job performance. The population in this study are employees of mining industries with a total of 203 employees as a sample. The determination of the sample was carried out using the non-probability sampling. The data analysis technique used is the Structural Equation Modeling (SEM) method. The statistical method used to test the hypothesis proposed in this study is Partial Least Square (PLS) with the help of the SmartPLS. Based on the results of the analysis it was found that job training, promotion, motivation had a significant effect on job satisfaction but rewards have a negative effect on job satisfaction, and job satisfaction had a significant effect on performance.